1992
DOI: 10.3109/17453679209154780
|View full text |Cite
|
Sign up to set email alerts
|

Strain, stress and stretch of peripheral nerve Rabbit experiments in vitro and in vivo

Abstract: Mechanical stretching is known to cause morphologic and functional changes in peripheral nerve. The points at which these changes occur, however, are not clearly defined and reported data are conflicting. The studies presented in this paper provide a basic understanding of the biomechanical properties, stretch-injury patterns, and changes of conduction properties of peripheral nerves due to stretching. Our studies showed that peripheral nerves exhibited non-linear stress-strain characteristics when placed unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
2
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(159 citation statements)
references
References 20 publications
3
145
2
9
Order By: Relevance
“…We found that the nerve cords break last during fission (Fig.S7). Because their diameter is only 50µm (Fig.S7), this implies stresses in the MPa range, similar to what has been reported as the tensile strength limit for nerve tissues in other organisms (25,31).…”
Section: Scale Bar =3mm (G) Time Dependences Of Head Length and Waistsupporting
confidence: 79%
See 1 more Smart Citation
“…We found that the nerve cords break last during fission (Fig.S7). Because their diameter is only 50µm (Fig.S7), this implies stresses in the MPa range, similar to what has been reported as the tensile strength limit for nerve tissues in other organisms (25,31).…”
Section: Scale Bar =3mm (G) Time Dependences Of Head Length and Waistsupporting
confidence: 79%
“…The rupture stresses we found are in the kPa range, which is orders of magnitude lower than stresses previously reported for rupture of tissues in other animals (25,26). It is possible that biological processes proceeding or accompanying waist formation weaken the waist and lower the required rupture stresses.…”
Section: Scale Bar =3mm (G) Time Dependences Of Head Length and Waistcontrasting
confidence: 64%
“…Denervation may result from compromise of nerve microcirculation. A minimal stretch of perturbed nerve tissue may add further hypoxia and concomitant nerve damage [23]. It seems therefore reasonable to propose that if a nerve root were compressed, hypoxic and oedematous, using a mobilisation technique implying further tensile stress would have a detrimental effect.…”
Section: Discussionmentioning
confidence: 99%
“…20 Based on the literature, this tension may adversely affect the central nervous system and nerve root function due to the absence of the perineurium, which is the primary load carrying structure. 21 The work of Harrison et al was pioneering in regard to the association between the extension position and the normal biomechanics of the nervous system. [22][23][24] Although, the extension traction has become more popular, 25,26 the extension position is still questioned in treating CR.…”
Section: Introductionmentioning
confidence: 99%